In Fact, It's a Matter of Opinion: Determining a Distinction Between Fact and Opinion within the New Zealand Defence of Honest Opinion - Riseley, Wendy J (Victoria University of Wellington Law Review, 2014)
This article discusses the distinction between fact and opinion within the defence of honest opinion. It is argued that the classic legal tests for determining that distinction are largely unhelpful and produce unpredictable results, which trigger a chilling effect on speech. This article advocates for an adaptation of the four-factor totality of circumstances test, established in Ollman v Evans, to be inserted into the Defamation Act 1992. This would provide more clarity, consistency and predictability for the defence of honest opinion in New Zealand, thereby better supporting freedom of expression under s 14 of the New Zealand Bill of Rights Act 1990.